Enumeration of rooted 3-connected bipartite planar maps - Noy, Marc; Requilé, Clément; Rué, Juanjo (Comptes Rendus. Mathématique)
We provide the first solution to the problem of counting rooted 3-connected bipartite planar maps. Our starting point is the enumeration of bicoloured planar maps according to the number of edges and monochromatic edges, following Bernardi and Bousquet-Mélou [J. Comb. Theory Ser. B, 101 (2011), 315–377]. The decomposition of a map into 2- and 3-connected components allows us to obtain the generating functions of 2- and 3-connected bicoloured maps. Setting to zero the variable marking monochromatic edges we obtain the generating function of 3-connected bipartite maps, which is algebraic of degree 26. We deduce from it an asymptotic estimate for the number of 3-connected bipartite planar maps of the form $t\, n^{-5/2}γ ^n$, where $γ = ρ ^{-1} ≈ 2.40958$ and $ρ ≈ 0.41501$ is an algebraic number of degree $10$.